Extrafollicular Adenomatoid Odontogenic Tumors: A Series of Five Rare Cases with an Insight into Its Clinicopathological Aspects - Debarati Ray; Snehanjan Sarangi; Tathagata Bhattacharjee; Jay Gopal Ray (Contemporary Clinical Dentistry)
Adenomatoid odontogenic tumors (AOT), first described by Steensland in 1905, are benign, slowly enlarging, nonaggressive, odontogenic epithelial neoplasms comprising 3%–7% of all odontogenic tumors. They tend to originate from the dental lamina remnants or the reduced enamel epithelium. Mutation at codon 12 of KRAS oncogene (Kirsten rat sarcoma viral oncogene homolog) plays a pivotal role in the pathogenesis. AOTs demonstrate three clinicopathological spectrums, namely follicular, extrafollicular, and peripheral. The extrafollicular AOTs are hypothesized to originate from a stimulus triggering the dental lamina remnants. While intraosseous follicular AOTs are fairly common (70.8%), the extrafollicular counterparts are infrequent (24%), and novel entities that may mimic other lesions due to the absence of tooth inside. Herein, we elucidate a series of five unique extrafollicular AOT cases with a relevant emphasis on its pathogenesis and clinico-radiological aspects. This report aims to add another significant record to the literature pertaining to the compilation of extrafollicular AOTs.